Influence of Chemical Modification on Structural, Morphological, Thermal, and Weathering Behavior of Eulaliopsis Binata Fiber and Its Composites. Issue 15 (23rd November 2022) - Pradhan, Subhrajit; Prakash, Ved; Acharya, Samir Kumar
ABSTRACT: In the present investigation, the influence of chemical treatment on the structural, morphological, thermal, and weathering behavior Eulaliopsis Binata (EB) fiber was studied. Composites were fabricated containing both untreated and chemically treated (with acetone, alkali, and benzoyl chloride) EB fibers. The mechanical characterization of the developed composites was carried out for both treated and untreated EB fiber composites to assess the effect of chemical modification on the mechanical properties. The maximum tensile and flexural strength were observed for benzoylated fiber composites. The percentage increase in the tensile and flexural strength of 30 weight fraction EB fiber composites was found to be 43.2% and 47.05% with respect to untreated fiber composites. The fractured surfaces of the specimens were studied using a Scanning Electron Microscope (SEM) to explore the fracture mechanisms of the developed composites.